Silver Nanoparticle Applications : In the Fabrication and Design of Medical and Biosensing Devices - Alarcon, Emilio I.; Griffith, May; Udekwu, Klas I. (Engineering Materials,, 2015)
Exploring the synthesis, characterization, surface manipulation, electron transfer, and biological activity of silver nanoparticles,  this book examines the fundamentals of  the properties and synthesis of these particles. With a renewed interest in silver nanoparticles, this book addresses the need to understand their potential in industrial, medical, and other applications. It is divided into six chapters, each written by an expert and providing a comprehensive review of the topic while detailing recent advances made in each specific area. These topics include surface plasmon band, synthesis and characterization, Surface-enhanced Raman spectroscopy (SERS) and plasmon resonance mediated processes, photocatalysis, biomedical applications and biological activity.  It also presents the current state of the art, challenges, and future trends of catalysis, sensing, and biomedical applications. 'Silver Nanoparticle Applications' provides an invaluable reference work and introduction for chemists, biologists, physicists, and biomedical researchers who are interested in exploring the uses and applications of silver nanoparticles. It is also intended for students, researchers and professionals interested in nanotechnology.